Mitochondrial Dysfunction Is Inducible in Lymphoblastoid Cell Lines From Children With Autism and May Involve the TORC1 Pathway - Bennuri, Sirish C.; Rose, Shannon; Frye, Richard E. (Frontiers in Psychiatry, 2019)
We previous developed a lymphoblastoid cell line (LCL) model of mitochondrial dysfunction in Autism Spectrum Disorder (ASD); some individuals with ASD showed mitochondrial dysfunction (AD-A) while other individuals (AD-N) demonstrated mitochondrial respiration similar to controls (CNT). To test the hypothesis that mitochondrial dysfunction could be a consequence of environmental exposures through chronic elevations in reactive oxygen species (ROS), we exposed LCLs to prolonged ROS. We also examined expression of metabolic regulatory genes and the modulating effect of the mechanistic target of rapamycin (mTOR) pathway. Prolonged ROS exposure induced or worsened mitochondrial dysfunction in all LCL groups. Expression of genes associated with ROS protection were elevated in both AD-N and AD-A LCLs but mitochondrial fission/fusion and mitoplasticity gene expression was only increased in AD-N LCLs. Partial least squares discriminant analysis showed that mTOR, UCP2, SIRT1 and MFN2 gene expression differentiated LCL groups. Low-dose rapamycin (0.1nM) normalized respiration with the magnitude of this normalization greater for AD-A LCLs, suggesting that the TORC1 pathway may have a different dynamic range for regulating mitochondrial activity in individuals with ASD with and without mitochondrial dysfunction, potentially related to S6K1 regulation. Understanding pathways that underlie mitochondrial dysfunction in ASD may lead to novel treatments.